Patient Time Spent With Professional Medical Interpreters and the Care Experiences of Patients With Limited English Proficiency - Pamela Torresdey; Jacob Chen; Hector P. Rodriguez (SAGE Publishing, 2024)
Introduction/Objectives: More time spent with interpreters may support clinician-patient communication for patients with limited English proficiency (LEP), especially when interpreter support before and after clinical encounters is considered. We assessed whether more time spent with interpreters is associated with better patient-reported experiences of clinician-patient communication and interpreter support among patients with LEP. Methods: Patients with LEP (n = 338) were surveyed about their experiences with both the clinician and interpreter. Duration of interpreter support during the encounter (in min) and auxiliary time spent before and after encounters supporting patients (in min) were documented by interpreters. Multivariable linear regression models were estimated to assess the association of the time duration of interpreter support and patient experiences of (1) clinician-patient communication, and (2) interpreter support, controlling for patient and encounter characteristics. Results: The average encounter duration was 47.7 min (standard deviation, SD = 25.1), the average auxiliary time was 43.8 min (SD = 16.4), and the average total interpreter time was 91.1 min (SD = 28.6). LEP patients reported better experiences of interpreter support with a mean score of 97.4 out of 100 (SD = 6.99) compared to clinician-patient communication, with a mean score of 93.7 out of 100 (SD = 14.1). In adjusted analyses, total patient time spent with an interpreter was associated with better patient experiences of clinician-patient communication (β = 7.23, P  < .01) when auxiliary time spent by interpreters supporting patients before and after the encounter was considered, but not when only the encounter time was considered. Conclusions: Longer duration of time spent with an interpreter was associated with better clinician-patient communication for patients with LEP when time spent with an interpreter before and after the clinician encounter is considered. Policymakers should consider reimbursing health care organizations for time interpreters spend providing patient navigation and other support beyond clinical encounters.